2018
DOI: 10.1002/ente.201800280
|View full text |Cite
|
Sign up to set email alerts
|

Defective Bi2WO6‐Supported Cu Nanoparticles as Efficient and Stable Photoelectrocatalytic for Water Splitting in Near‐Neutral Media

Abstract: Defective Bi2WO6‐supported Cu nanoparticles photoelectrocatalyst were successfully synthesized via an etching approach by using NaBH4 as reducing agent. The as‐prepared Cu/Bi2WO6‐1 was dominated by CuO and Cu and Cu/Bi2WO6‐2 was dominated by metallic Cu, confirmed by XPS and TEM analyses. These etching pretreatments also induced the formation of defect sites such as oxygen vacancies and W5+. The presence of oxygen vacancies could significantly increase the photogenerated electrons capture abilities. Metallic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 78 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…In addition, other Cu‐based catalysts have also been utilized in water splitting with plasmon‐enhanced activity, such as Cu/TiO 2 , Cu/ZnO, plate‐like Cu@Ni core‐shell cocatalyst, Cu/SiTiO 3 , Cu/defective‐Bi 2 WO 6 , Cu NPs/CuFe 2 O 4 , and so on. [ 10–16 ]…”
Section: Localized Surface Plasmon Resonance‐mediated Reactions Over Cu‐based Plasmonic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other Cu‐based catalysts have also been utilized in water splitting with plasmon‐enhanced activity, such as Cu/TiO 2 , Cu/ZnO, plate‐like Cu@Ni core‐shell cocatalyst, Cu/SiTiO 3 , Cu/defective‐Bi 2 WO 6 , Cu NPs/CuFe 2 O 4 , and so on. [ 10–16 ]…”
Section: Localized Surface Plasmon Resonance‐mediated Reactions Over Cu‐based Plasmonic Catalystsmentioning
confidence: 99%
“…[ 5,6 ] In the last decade, plasmonic metals have been discovered as superior photocatalysts in a variety of catalytic reactions, including water splitting, CO 2 reduction reaction (CO 2 RR), N 2 photofixation, oxidation reaction, NH 3 decomposition, and so on. [ 7–36 ] Plasmonic metals are able to efficiently harvest and convert solar energy via localized surface plasmon resonance (LSPR). [ 37–40 ] Compared with conventional thermal‐driven catalysis, plasmonic catalysis can significantly decrease the reaction temperature to achieve desired catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of self-healing catalysis are (i) any water source may be used for water splitting, (ii) the fabrication of buried junction devices is facilitated owing to greater materials stability offered by a neutral water environment, (iii) the reduced liability associated with technology advancement, and (iv) the ability to interface water splitting catalysis to biology. For these reasons, buried junction PECs comprising earth-abundant materials that operate in water at near-neutral conditions are now being adopted as the preferred approach for solar-driven water-splitting. ,, Moreover, the high solar energy efficiencies afforded by H 2 generation with a buried junction device allow for much higher efficiencies for carbon fixation from CO 2 (vide infra).…”
Section: The Artificial Leaf: Solar-driven Water Splittingmentioning
confidence: 99%
“…46 The UV-vis spectrum of Cu-Bi 2 WO 6 showed that there is a strong absorption peak at about 305 nm, while there is a wide and weak absorption peak at 670 nm due to the SPR absorption of Cu. 22 FTIR measurements were done to confirm the formation of the covalent link between the CoTAPc and GO as shown in Figure 1H. The characteristic peak of the -NH 2 is recorded at 1608 cm −1 for Co-TAPc.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 In addition, Bi 2 WO 6 owns relatively narrow bandgap (2.8 eV), which promote the separation of photogenerated electron-hole pairs. 22 However, the further enhancement of PEC performance of Bi 2 WO 6 is a major challenge due to unfavorable efficiency of light absorption, high recombination rate of photoexcited electron-hole and poor electron transport efficiency. Various approaches have been reported to deal with the above disadvantages, such as coupling, 23 doping, 24 surface functionalization, 25 heterojunction, 26 and so on.…”
mentioning
confidence: 99%